A systematic analysis of disability inclusion in domestic climate policies - Sébastien Jodoin; Amanda Bowie-Edwards; Katherine Lofts; Sajneet Mangat; Bianca Adjei; Alexandra Lesnikowski (npj Climate Action)
Abstract We provide the first systematic analysis of whether, how, and to what extent people with disabilities and their human rights are included in two subsets of climate policies adopted by 195 parties to the Paris Agreement. We found that only 41 parties mention people with disabilities in their nationally determined contributions (NDCs), whereas only 75 do so in their adaptation policies. Moreover, these references are rarely accompanied by concrete measures to include people with disabilities, their rights, or their knowledge in climate decision-making. Our findings demonstrate that states are generally not abiding by their obligations to respect, protect, and fulfill the human rights of persons with disabilities under international and domestic law. This exposes people with disabilities to climate-related harm and reinforces, rather than disrupts, the inequities they face in societies around the world. It also fails to harness the multiple benefits associated with a disability-inclusive approach to climate action.